THE GIVING BREATH RELAXATION TECHNIQUES IN PASSIVE EXERCISE THERAPY REDUCE PAIN INTENSITY IN PATIENTS IN SECOND DEGREE BURNS SANGLAH HOSPITAL IN DENPASAR - Aryani, Kadek Agustini (Majalah Ilmiah Fisioterapi Indonesia, 2013)
The burn is a form of tissue damage caused by contact with heat sources. Pain is one of the clinical manifestations in the second degree burns. The research was conducted in Sanglah Hospital Burn Unit Denpasar. This research is experimental, randomized design with pre test and post test control group design. The samples were obtained for 24 people consisting of 12 persons of control group and 12 treatment groups. The sample was selected by randomized sampling technique. Independent variables in this study is a passive exercise therapy and breathing relaxation techniques. Dependent variable is the change in pain intensity as measured by the VAS scale. Data were analyzed with parametric statistical test with t test. The results obtained t value of 34.51 with an average value of 50.33, p of 0.00 (p <0.05) results showed that mean H0 rejected passive exercise therapy is effective in reducing pain in the second degree burns. In the intervention breathing and relaxation techniques of passive exercise therapy obtained t value of 63.44, an average of 66.50, p of 0.00 (p <0.05) showed a mean H0 rejected breathing relaxation techniques and exercise therapy is effective passive reduce pain intensity II degree burns. From the results showed no significant differences in the influence which intervention techniques at therapy relaxation breathing exercises reduce pain more effectively passive degree burns II because results obtained from the average difference in pain intensity decreased by 66.50 while in passive exercise therapy intervention gained an average decrease in pain intensity difference of 50.33.
Keywords: relaxation breathing techniques, passive exercise therapy, pain intensity,; second-degree burns.